2017
DOI: 10.1186/s13071-017-2400-5
|View full text |Cite
|
Sign up to set email alerts
|

Praziquantel treatment after Schistosoma japonicum infection maintains hepatic insulin sensitivity and improves glucose metabolism in mice

Abstract: BackgroundEpidemiological studies in China have revealed that Schistosoma japonicum infection is inversely correlated with metabolic syndrome, even after repeated chemotherapy with praziquantel (PZQ). We investigated the effect of chronic S. japonicum infection, PZQ chemotherapy, and soluble egg antigen (SEA) treatment on whole-body metabolic homeostasis and hepatic insulin sensitivity in mouse models.ResultsInfection with S. japonicum was found to increase whole-body and hepatic insulin sensitivity in mice. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 33 publications
1
29
0
Order By: Relevance
“…Our previous study showed that the whole-body and hepatic insulin sensitivity were decreased in S. japonicum -infected mice [5]. In consistence with this, the level of fasting blood glucose in mice was significantly decreased after S. japonicum infection (Fig.…”
Section: Resultssupporting
confidence: 57%
See 3 more Smart Citations
“…Our previous study showed that the whole-body and hepatic insulin sensitivity were decreased in S. japonicum -infected mice [5]. In consistence with this, the level of fasting blood glucose in mice was significantly decreased after S. japonicum infection (Fig.…”
Section: Resultssupporting
confidence: 57%
“…We previously reported that chronic exposure to S . japonicum induces a type 2 immune response in the liver and improved insulin sensitivity and glucose tolerance [5]. Here, we have further performed in-depth metabolic profiling, which showed that S .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hussaarts et al (7) reported that in mice with chronic obesity induced by a high-fat diet, chronic infection with Schistosoma mansoni decreased body weight, fat aggregation, and adipocyte volume and improved adipose tissue sensitivity to insulin in peripheral tissues. Luo et al (8) also reported that chronic S. japonicum infection with praziquantel chemotherapy protected against metabolic syndrome via a mechanism involving the enhancement of the Th2-type immune response. Hams et al (9) reported that ω-1, derived from recombinant S. mansoni eggs, improved the metabolic status of obese mice by the release of the Th2-type cytokine IL-33.…”
Section: Introductionmentioning
confidence: 98%